1997
DOI: 10.1111/j.1365-2133.1997.tb03735.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of monilethrix to the type II keratin gene cluster at chromosome 12q13 in three new families, including one with variable expressivity

Abstract: Monilethrix is an autosomal dominant disorder chiefly affecting hair. The degree of hair dystrophy is highly variable, as is the presence of additional features, such as follicular keratoscs. In three British families of monilethrix. linkage has recently been reported to the type II keratin gene cluster at chromosome 12ql 3. and it has been suggested that the disease is due to a defect in the hard keratins of hair and nail. If monilethrix is a keratin disorder, we would predict that some pedigrees might map to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…130,131 The gene for monilethrix is linked to the type II keratin gene cluster on chromosome 12q13. [132][133][134] Studies have isolated mutations in type II hair cortex keratins hHB6 and hHB1. The gene is divided structurally into a-helical rod domains, helix initiation motifs (HIM), and helix termination motifs (HTM).…”
Section: Trichorrhexis Invaginatamentioning
confidence: 99%
“…130,131 The gene for monilethrix is linked to the type II keratin gene cluster on chromosome 12q13. [132][133][134] Studies have isolated mutations in type II hair cortex keratins hHB6 and hHB1. The gene is divided structurally into a-helical rod domains, helix initiation motifs (HIM), and helix termination motifs (HTM).…”
Section: Trichorrhexis Invaginatamentioning
confidence: 99%
“…Previous ultrastructural hair studies of monilethrix patients suggested disturbances in keratin expression and ordered intermediate filament formation in trichocytes of both the hair matrix and the cortex of the hair shaft (Ito et al, 1990;De Berker et al, 1993). Further evidence for monilethrix as a possible keratin disease was provided by genetic linkage of several unrelated pedigrees to the type II keratin gene cluster on chromosome 12q13 (Healy et al, 1995;Stevens et al, 1996;Birch-Machin et al, 1997), 1 which also harbors the type II hair keratin genes (Rogers et al, 1995). At present, four human type II hair keratins have been characterized in our laboratory (Rogers et al, 1995(Rogers et al, , 1997.…”
mentioning
confidence: 99%
“…1 Because the hairs are very thin and fragile, they tend to fracture close to the scalp, producing dystrophic alopecia. 3 In the milder form, the disease involves only the occipital regions and the nape of the neck, but in the more severe form, the entire scalp, secondary sexual hair, eyebrows, eyelashes, and occasionally the nails may be affected. The variability of the monilethrix phenotype suggests that other factors also affect gene or disease expression.…”
Section: Introductionmentioning
confidence: 99%